2021
DOI: 10.2147/copd.s322144
|View full text |Cite
|
Sign up to set email alerts
|

Association of Systemic Inflammation with Depressive Symptoms in Individuals with COPD

Abstract: Rationale Depression is a prevalent comorbidity of chronic obstructive pulmonary disease (COPD) that, along with COPD, has been associated with inflammation. An association between inflammation and depression in COPD has not been validated in a large COPD cohort. Methods Individuals from the University of Pittsburgh SCCOR cohort and the COPDGene cohort with tobacco use history and airway obstruction (FEV 1 /FVC <0.7) were evaluated using the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The apparent reduction in depression and anxiety as people age may be due to a series of factors, Firstly older Participants may have di culties and Secondly they will considered that physical disabilities and functional limitations are uncommon after retirement. But younger patients may nd it di cult to accept lifestyle changes, leading to a higher risk of depression [13] .Previous studies have demonstrated elevated systemic in ammatory markers in COPD patients, including C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) [14]- [15] ,Recent literature has shown that adults with major depression are associated with elevated IL-1ß, IL-6, and CRP. A recent study of a sample of older adults showed that elevated levels of the in ammatory biomarker C-reactive protein are partly responsible for depressive symptoms and COPD [16] .Higher CRP were associated with an increased risk of depression in patients with COPD [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The apparent reduction in depression and anxiety as people age may be due to a series of factors, Firstly older Participants may have di culties and Secondly they will considered that physical disabilities and functional limitations are uncommon after retirement. But younger patients may nd it di cult to accept lifestyle changes, leading to a higher risk of depression [13] .Previous studies have demonstrated elevated systemic in ammatory markers in COPD patients, including C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) [14]- [15] ,Recent literature has shown that adults with major depression are associated with elevated IL-1ß, IL-6, and CRP. A recent study of a sample of older adults showed that elevated levels of the in ammatory biomarker C-reactive protein are partly responsible for depressive symptoms and COPD [16] .Higher CRP were associated with an increased risk of depression in patients with COPD [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study that analyzed induced sputum samples from COPD patients (n = 26) and healthy controls (n = 21) reported significantly elevated levels of IL-6, IL-8, IL-13, and monocyte chemoattractant protein (MCP)-1 in the airway of COPD patients compared to healthy controls [ 69 ]. Elevated IL-6 levels in plasma are linked to depressive symptoms in COPD, independent of airflow limitation and comorbid risk factors for depression [ 70 ]. In addition, soluble TNF receptor-1 (sTNFR-1) was significantly associated with depression in COPD [ 65 ], while depression ratings have been positively associated with plasma TNF-α levels in COPD [ 71 ].…”
Section: Underlying Mechanisms Associated With Mood Disorders In Copdmentioning
confidence: 99%
“…Patients with COPD often show psychiatric comorbidities, specifically: generalized anxiety, panic disorder, and depression (Su et al , 2017; Montserrat-Capdevila et al , 2018; Miravitlles et al , 2018; Puteikis et al , 2021; Strollo et al , 2021). These conditions are associated with poorer quality of life (QoL) (Spruit and Wouters, 2019), physical impairments, lower compliance to treatment plans, more severe exacerbation rates with more frequent emergency admissions and, ultimately, higher 30-day mortality compared to their counterparts without anxiety or depression (Pollok et al , 2019).…”
Section: Introductionmentioning
confidence: 99%